Association between anesthesia duration and outcome in dogs with surgically treated acute severe spinal cord injury caused by thoracolumbar intervertebral disk herniation. (17th May 2020) - Fenn, Joe; Ru, Hongyu; Jeffery, Nick D.; Moore, Sarah; Tipold, Andrea; Soebbeler, Franz J.; Wang‐Leandro, Adriano; Mariani, Christopher L.; Early, Peter J.; Muñana, Karen R.; Olby, Natasha J.
Abstract: Background: Retrospective research recently identified a possible relationship between duration of surgery and outcome in severely affected dogs treated surgically for acute thoracolumbar intervertebral disk herniation (TL‐IVDH). Hypothesis: That increased duration of surgery is associated with poorer outcome in dogs with absent pain perception treated surgically for TL‐IVDH. Animals: Two hundred ninety‐seven paraplegic dogs with absent pain perception surgically treated for acute TL‐IVDH. Methods: Retrospective cohort study. Medical records of 5 institutions were reviewed. Inclusion criteria were paraplegia with absence of pain perception, surgical treatment of TL‐IVDH, and 1‐year postoperative outcome (ambulatory: yes or no). Canine data, outcome, and surgery and total anesthesia duration were retrieved. Results: In this study, 183/297 (61.6%) dogs were ambulatory within 1 year, 114 (38.4%) dogs failed to recover, including 74 dogs (24.9%) euthanized because of progressive myelomalacia. Median anesthesia duration in dogs that regained ambulation within 1 year of surgery (4.0 hours, interquartile range [IQR] 3.2‐5.1) was significantly shorter than those that did not (4.5 hours, IQR 3.7‐5.6, P = .01). Multivariable logistic regression demonstrated a significant negative association between both duration of surgery and total anesthesia time and ambulation at 1 year when controlling for body weight and number of disk spaces operated on. Conclusions and Clinical Importance: Findings support a negative association between increased duration of anesthesia and outcome in this group of dogs. However, the retrospective nature of the data does not imply a causal relationship.